Avaliação do processo fotocatalítico na desinfecção de efluentes anaeróbios de águas residuárias - Reinaldo, Myrthis Virgínia Alves de Almeida (2006)
This research was accomplished with the purpose of studying the acting of a process developed for environmental disinfection, contributing for disinfection of wastewaters from anaerobic treatment systems of sanitary sewers. This process used the heterogeneous photocatalysis, that consists of the oxidation of organic pollutants through the generation of radicals hidroxila ( OH), highly oxidizers, which is gotten with the aid of a semiconductor and a UV radiation source. The semiconductor was the titanium dioxide (TiO2) and the source of energy from artificial luminous source (UV lamp) and natural (Sun) of ultraviolet radiation. Two types of reactors were used: a reactor type concentric tubes containing a 15W bactericidal UV lamp inside, treating wastewaters coming of two systems: UASB and Anaerobic Filter of Chicanes, with a flow of recirculation of 72 L.h-1 for 2 hours. In this reactor was made experiments with and without TiO2 in suspension. And a TiO2 impregnated plate reactor, treating wastewater of the anaerobic filter of chicanes, working in four different flow of recirculation: 13,2L.h-1, 25L.h-1, 42L.h-1 and 75L.h-1, for 4 hours of exposed to the sunlight. For both were evaluated the removal efficiencies of the fecal contamination indicative microorganisms - thermotolerants coliforms, and the rate of bacterial inativation through the study of the kinetic constant (k) and analyzed the physical and chemical parameters corresponding to the variation of the temperature, pH, electric conductivity (CE), total alkalinity and to bicarbonate, total nitrogen Kjeldahl (TNK), ammonia (NH3), total phosphor and orthophosphate, solids and your fractions, volatile greasiest acids (AGV) and removal of the organic matter (QDO). The kinetics study of the bacterial inativation (k) it revealed the best acting, in the concentric tubes reactor, for the experiment with photocatalysis using the anaerobic filter of chicanes wastewater. Already in the impregnated plate reactor, the best acting was observed in the 25L.h-1 flow, with 100% thermotolerants coliforms removed. The experiment with impregnated plate reactor it was shown efficient in the removal of the nitrogen compounds TNK and Ammonia. The smallest removal efficiency of thermotolerants coliforms of the UASB wastewater, in the concentric tubes reactor, was due to the high concentration of solids in suspension of the secondary wastewater, what block the uniformity of the UV radiation penetration. High evaporation rates, frequent in the experiments with the impregnated plate reactor, they caused increase in the final concentration of some parameters. The process of the heterogeneous photocatalysis is an efficient alternative method for the disinfection of tertiary wastewater with low concentration of solids in suspension.